(untitled) (INNOVATIVE ECONOMY, 2020)
Korkuna O.I., Nykyha O.V., Pidvalna O.H. INNOVATIVE DEVELOPMENT AS A DIRECTION OF FUNCTIONING OF REGIONAL TOURIST SYSTEMS Purpose. The aim of the article is generalization of conceptual bases of innovative development of tourism at the regional level, allocation of perspective directions of innovative activity in functioning of regional tourist systems of Ukraine. Methodology of research. The following methods are used achieve this goal the: analysis of scientific literature ‒ to study approaches to understanding the essence and structure of the concepts “innovation”, “innovative activity”, “innovative development”, features of innovation in tourism; generalization and synthesis ‒ to substantiate the conceptual foundations of innovative development of regional tourist systems. Findings. It is proved that innovation is an important factor and result of modern tourism, and innovation development should be considered as a priority to increase the competitiveness of tourism enterprises, destinations, regions and countries; it has a complex structure and systemic nature. It is substantiated that the main directions of innovative development of regional tourist systems are: formation of innovative infrastructure (in particular, in the form of tourist clusters), intensification of innovative activity at enterprises, increase of efficiency of introduction and use of innovative technologies, wider involvement of administrative, scientific and educational subsystems to the processes of generating and supporting innovation. Originality. Theoretical and methodological bases of research of innovative development of tourism at the regional level are improved. The concept of innovative factors of regional tourist systems has been further developed. Practical value. The results of the study can be used in the practice of regional and state management of tourism development, strategic planning, and in the activities of tourism businesses. Theoretical and methodological generalizations can be the basis for further researches. Key words: innovative development, regional tourist system, approach, concept, cluster.